Concepts and Challenges in Digitalizing the Land Management System in Indonesia - Putri, Andrieta Isabella Edwina; Putri, Naurah Dwirengganis Riata (Notaire, 2024)
AbstractThe concept and challenges of digitalizing the land management system in Indonesia are crucial due to the importance of land as a fundamental factor in Indonesian society. A suitable land management system is necessary to accommodate the evolving times, providing certainty and legal protection for its rights holders. This article aims to discuss the concept of modernization in land data management, including the initiation of electronic signatures, electronic Mortgage Rights (HT-el), and the policy of Electronic Land Certificates, which are scheduled to be implemented soon. The discussion will also address the challenges and difficulties in the implementation of digitalization in the field of land related to it. Through qualitative analysis, the research findings reveal that electronic signatures have begun to be applied in several institutions in Indonesia, including in land governance under the Ministry of Agrarian and Spatial Planning/National Land Agency. The HT-el system is also operational, although there are still some challenges in its implementation. However, there are issues related to the transition to Electronic Land Certificates, including concerns about the security of land rights certificate data and the regulation mandating the withdrawal of all physical land rights certificates to be stored in land offices. The implication of this research is that the digitalization of the land management system aims to optimize land services for rights holders and related third parties. However, there are still obstacles, both in terms of infrastructure and practicalities, that need to be addressed to achieve comprehensive digital transformation of the land management system in Indonesia. This article has not been previously published in whole or in part in the form of a journal, working paper, or other published format.Keywords: Land Management; Digitalization; Electronic Signatures; Electronic Mortgage; Electronic Land Certificate.